Health Maintenance In The New Normal: An Analysis Of University Students' Awareness Using Clustering And Naïve Bayes - Tanadi, Fiona; Sunardi Oetama, Raymond (Publisher Cv. Inara, 2023)
The new normal has posed significant challenges for students in maintaining their health. To address this issue, this study aimed to examine the awareness of university students in maintaining their health during this period using clustering and Naïve Bayes methods. The results of the study revealed two distinct clusters,